2018
DOI: 10.1038/s41598-018-34140-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deepwater Horizon Crude Oil Water Accommodated Fraction on Olfactory Function in the Atlantic Stingray, Hypanus sabinus

Abstract: The Deepwater Horizon oil spill was the largest accidental marine oil spill in history, releasing nearly 5 million barrels of crude oil. Crude oil causes both lethal and sublethal effects on marine organisms, and sensory systems have the potential to be strongly affected. Marine fishes rely upon the effective functioning of their sensory systems for detection of prey, mates, and predators. However, despite the obvious importance of sensory systems, the impact of crude oil exposure upon sensory function remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 55 publications
0
19
2
1
Order By: Relevance
“…Moreover, damage to the higher order central nervous system processing was implicated in this decreased oil avoidance behavior. Olfactory damage is also known to occur with oil exposure in some fishes (such as Atlantic stingrays, Cave et al 2018) and reduced recognition of threats via these cues is also possible (Schlenker et al 2019b). Whether highly weathered crude oil elicits similar effects and the specific chemical constituents in oil involved in these detrimental physiological changes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, damage to the higher order central nervous system processing was implicated in this decreased oil avoidance behavior. Olfactory damage is also known to occur with oil exposure in some fishes (such as Atlantic stingrays, Cave et al 2018) and reduced recognition of threats via these cues is also possible (Schlenker et al 2019b). Whether highly weathered crude oil elicits similar effects and the specific chemical constituents in oil involved in these detrimental physiological changes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that oil exposure can inhibit or damage sensory mechanisms used by fishes to detect oil. For example, exposure to the water-accommodated fraction of oil in Atlantic stingrays Hypanus sabinus damaged olfactory function (Cave et al 2018). After oil exposure, bicolor damselfish Stegastes partitus showed a reduction in the response to conspecific alarm cues (Schlenker et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Olfaction. There were clear effects of oil exposure on olfaction in fish (Cave and Kajiura 2018), an area largely unexplored prior to the DWH oil spill. Studies in Atlantic stingrays (Hypanus sabinus) reported an average decrease in magnitude of the olfactory response by 45.8% after 48 hr exposure to oil mimicking the concentrations found in the coastal regions.…”
Section: Fishmentioning
confidence: 99%
“…Exposure to anthropogenic contaminants also poses threats to the performance and health of elasmobranch fishes in unexpected ways. For example, the olfactory sensitivity of Atlantic stingray to amino acids is reduced after acute exposure to mixtures of crude oil, which may impair their ability to forage successfully (Cave and Kajiura, 2018).…”
Section: Future Directionsmentioning
confidence: 99%